How intermittent presentation affects conscious perceptual reversals of ambiguous figures - Zheng, Meihong (Springer International Publishing AG, 2013)
Continually observing an ambiguous figure, we can perceive reversals between different interpretations. How perceptual reversals change when an ambiguous stimulus is presented intermittently? Since no reversal can be consciously perceived during off-periods, we use net Average Reversal Interval (netARI) but not usual average reversal interval to measure the perceptual reversal rate. NetARI is calculated by dividing accumulated time of on-periods by the number of reversals. The results are: (1) presenting an ambiguous figure intermittently increased the perceptual reversal rate; (2) the longer the exposure of Necker cube, the slower the perceptual reversal rate was, and when on-periods were longer as 15 s, the perceptual reversal rate was slowed down and was almost same to that in the continuous case; (3) the length of off-periods (which ranged from 1 s to 5 s in the present study) did not affect the reversal rate.